Design of low-cost ionic liquids for lignocellulosic biomass pretreatment. Issue 3 (12th January 2015) - George, Anthe; Brandt, Agnieszka; Tran, Kim; Zahari, Shahrul M. S. Nizan S.; Klein-Marcuschamer, Daniel; Sun, Ning; Sathitsuksanoh, Noppadon; Shi, Jian; Stavila, Vitalie; Parthasarathi, Ramakrishnan; Singh, Seema; Holmes, Bradley M.; et al.
Abstract : The cost of ionic liquids (ILs) is a barrier to utilization in cellulosic biorefinery pretreatment. Our low-cost [HSO4 ] − ILs are nearly as efficient as standard [OAc] options. Abstract : The cost of ionic liquids (ILs) is one of the main impediments to IL utilization in the cellulosic biorefinery, especially in the pretreatment step. In this study, a number of ionic liquids were synthesized with the goal of optimizing solvent cost and stability whilst demonstrating promising processing potential. To achieve this, inexpensive feedstocks such as sulfuric acid and simple amines were combined into a range of protic ionic liquids containing the hydrogen sulfate [HSO4 ] − anion. The performance of these ionic liquids was compared to a benchmark system containing the IL 1-ethyl-3-methylimidazolium acetate [C2 C1 im][OAc]. The highest saccharification yields were observed for the triethylammonium hydrogen sulfate IL, which was 75% as effective as the benchmark system. Techno-economic modeling revealed that this promising and yet to be optimized yield was achieved at a fraction of the processing cost. This study demonstrates that some ILs can compete with the cheapest pretreatment chemicals, such as ammonia, in terms of effectiveness and process cost, removing IL cost as a barrier to the economic viability of IL-based biorefineries.